Specifying Big Data Benchmarks First Workshop, WBDB 2012, San Jose, CA, USA, May 8-9, 2012, and Second Workshop, WBDB 2012, Pune, India, December 17-18, 2012, Revised Selected Papers - Rabl, Tilmann; Poess, Meikel; Baru, Chaitanya; Jacobsen, Hans-Arno.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
This book constitutes the thoroughly refereed revised selected papers of the First Workshop on Big Data Benchmarks, WBDB 2012, held in San Jose, CA, USA, in May 2012 and the Second Workshop on Big Data Benchmarks, WBDB 2012, held in Pune, India, in December 2012. The 14 revised papers presented were carefully reviewed and selected from 60 submissions. The papers are organized in topical sections on benchmarking, foundations and tools; domain specific benchmarking; benchmarking hardware; and endo-to-end big data benchmarks.
Benchmarking, Foundations and Tools -- Domain Specific Benchmarking -- Benchmarking Hardware -- End-to-End Big Data Benchmarks.
Keywords: Computer science; Database management; Data mining; Information storage and retrieval systems; Computer Science; Database Management; Data Mining and Knowledge Discovery; Information Storage and Retrieval